Study on Internal Force of Tunnel Segment by Considering the Influence of Joints. (31st October 2020) - Dong, Linwei; Yang, Zhiyong; Wang, Zhenyong; Ding, Yaowen; Qi, Weiqiang
Abstract : The mechanical performance of segments is an important aspect of the safety of tunnel structures. Study on the internal force of tunnel segment by considering the influence of joints is beneficial for obtaining a better understanding of the influence of various factors on the internal force of the segments. Based on the mechanical characteristics of shield segment joints, in which the displacements and stiffness are discontinuous, a mechanical model of the segment component under the constraints of elastic support was established. The elastic centre method and the principle of superposition were used to quantify the influence of joint displacements on the internal force of the segment component. Combined with a practical engineering application, the internal force of the segment component with joint rotation and dislocation was analysed. The displacements of the segment joints cause an unloading effect of the corresponding internal force of the joints, leading to internal force redistribution of each segment cross section. According to the spline interpolation results of the load test data of the segment joints, the internal force of the segment component under an external load is solved by the iterative method.